The Potential of Renewable Energy in Timor-Leste: An Assessment for Biomass - Lelis Gonzaga Fraga; José Carlos F. Teixeira; Manuel Eduardo C. Ferreira (Energies, 2019)
This paper assesses the potential of biomass energy resources in Timor-Leste (TL). Although other renewable energy sources are mentioned in this article, such as wind energy, solar energy, hydropower, bioenergy, including bioethanol and biogas, the main goal is to gather the data on biomass in TL and provide such data as useful information for a wide range of end-users. The current evaluation is based on various sources which include previous assessments on biomass and other renewable sources. The energy potential of biomass in TL apart that resulting from vegetation or flora and animals is also derived from agricultural waste, such as waste from rice, corn, and coffee. The analyses also include the contribution of agricultural waste, animal waste, and that from urban waste. The results from this article show that the potential of usable biomass energy in TL from forestry and agriculture is 1.68 × 106 toe/year, animal waste is 4.81 × 103 toe/year, and urban solid waste amounts to 9.55 × 103 toe/year. In addition, it is concluded that biomass alone can fully replace fossil fuels for electricity generation.